2010
DOI: 10.1007/s10549-010-1202-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry compared to cytosol assays for determination of estrogen receptor and prediction of the long-term effect of adjuvant tamoxifen

Abstract: and prediction of response to adjuvant tamoxifen treatment in postmenopausal women with early stage invasive breast cancer. Patients and methodsThe Stockholm Breast Cancer Study Group conducted a randomized trial during 1976 through 1990 comparing adjuvant tamoxifen versus control. The patients were stratified according to tumor size and lymph node status in high risk and low risk groups. In this study we evaluated 683 patients with "low risk" breast cancer (size≤30 mm, lymph node-negative) for whom ER status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 32 publications
4
53
0
1
Order By: Relevance
“…Cut-off level for ER positivity was 0.05 fmol/μg DNA. Isoelectric focusing/EIA and IHC data have been shown to be comparable [15]. Human epidermal growth factor receptor 2 (HER2) protein was quantified retrospectively by flow cytometry as described previously [16] and HER2 amplification was determined with quantitative Real-Time PCR [17].…”
Section: Evaluation Of Er Her2 Pik3ca and Paktmentioning
confidence: 99%
“…Cut-off level for ER positivity was 0.05 fmol/μg DNA. Isoelectric focusing/EIA and IHC data have been shown to be comparable [15]. Human epidermal growth factor receptor 2 (HER2) protein was quantified retrospectively by flow cytometry as described previously [16] and HER2 amplification was determined with quantitative Real-Time PCR [17].…”
Section: Evaluation Of Er Her2 Pik3ca and Paktmentioning
confidence: 99%
“…Among postmenopausal women, earlier studies have shown a significant trend in reduction of recurrence rate with higher ER levels among tamoxifen treated, supporting the significance of stronger ER content in endocrine treatment [5][6][7][8].…”
Section: Discussionmentioning
confidence: 92%
“…Remaining research questions include the benefit of LHRH agonists, in addition to tamoxifen, and if LHRH agonists have a role among those not achieving amenorrhea during cytotoxic chemotherapy. Moreover, efficacy of endocrine treament in relation to estrogen receptor (ER) status is mainly established among postmenopausal women, and the different endocrine milieu in premenopausal women may affect the predictive ability of ER status [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown a direct linear relationship between er concentration and survival 3,8,14,16,18,[23][24][25][26] . However, very few studies have supported the use of antihormonal treatment in breast cancer patients whose tumours are weakly positive for er (3-9 fmol/mg cytosol protein by lba or 1%-9% by ihc assay).…”
Section: Discussionmentioning
confidence: 99%
“…Pts = patients; HR = hazard ratio; CI = confidence interval. those used in most previous studies (femtomoles per microgram of dna rather than femtomoles per milligram of cytosol protein) 26 .…”
Section: Discussionmentioning
confidence: 99%